IMPLEMENTASI SISTEM PERPUSTAKAAN MANDIRI DIGITAL DENGAN TEKNOLOGI BARCODE DAN FINGERPRINT DALAM UPAYA MENINGKATKAN EFISIENSI LAYANAN - Sibero, Alexander Fernando Kawas; Manurung, Immanuel Hormat Gunawan; Zalogo, Marianus Apner (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2026)
A library information system is a computerized system for managing books and other library collections. It handles transactions such as borrowing, returning, renewing, and so on. The user of a library information system is generally an administrator who is solely responsible for managing the system. Library members simply select library collections and present their membership cards to complete transactions. The concept of an independent library information system is based on the system's high dependence on administrators, so that in certain situations, officers may not be able to provide services to members. Furthermore, transaction processing time can also be improved by using an independent system. Barcode technology is used to read library collection data, and fingerprint technology is efficient in identifying and verifying member data. The increasingly fast service time illustrates the benefits of implementing fingerprints and barcodes in library information systems. Likewise, increasing user satisfaction indicates that fingerprint and barcode technology have a significant impact on the research location. The results of the evaluation of service time and user satisfaction in this study are expected to open up further research opportunities in the field of library information systems.